Tanggung Jawab Hukum Notaris Yang Bekerjasama Dengan Pihak Lain Ditinjau Dari Undang-Undang Jabatan Notaris Dan Kode Etik Notaris - Chika Anissa Heptasari (Officium Notarium, 2021)
Due to the growing number of the Notary profession in the globalization era, it requires the Notary profession to be skilled, so that many Notaries build relationships with financial institutions or banks and also cooperate with individuals in finding customers. This makes the Notary no longer an independent official because of the dependence on the parties and contrary to the rules of the Notary Position Act and also the rules in the Notary Code of Ethics. The problems studied are: What are the sanctions against Notaries who cooperate with other parties in terms of the Law on Notary Positions and the Notary Code of Ethics and what are the driving factors that influence Notaries to cooperate with other parties. The research method uses an empirical approach as well as primary, secondary and tertiary legal materials. The conclusion in this study is that a Notary who cooperates with financial institutions by sending a letter of application for cooperation is not in accordance with the Law on Notary Positions in Article 16 paragraph (1) letter a on the independency of a Notary and the rules in the Notary code of ethics in Article 4 paragraph (3) on prohibitions of marketing activities that are included in self-promotion in the form of printed medias. Meanwhile, in the event that a Notary cooperates with an individual, it is not in accordance with the UUJN in Article 16 Paragraph 1 letter a and letter m, namely the deed must be read to the applicants unless the applicants wish otherwise because the applicants have read it themselves.Key Word: Notary, Cooperation, Sanctions AbstrakAkibat banyak lahirnya profesi Notaris di era globalisasi menuntut profesi Notaris untuk terampil, sehingga banyak dari beberapa Notaris yang membangun relasi dengan lembaga keuangan atau bank dan juga bekerjasama dengan pihak perorangan dalam mencari nasabah. Hal ini membuat Notaris tidak lagi menjadi pejabat yang independen karena adanya ketergantungan terhadap para pihak serta bertentangan dengan aturan Undang-Undang Jabatan Notaris dan juga aturan dalam Kode Etik Notaris. Adapun permasalahan yang diteliti adalah, Apa sanksi terhadap Notaris yang melakukan kerjasama dengan pihak lain ditinjau dari Undang Undang Jabatan Notaris dan Kode Etik Notaris, serta apa faktor pendorong yang mempengaruhi Notaris baekerjasama dengan pihak lain. Metode penelitian menggunakan pendekatan empiris serta bahan hukum primer, sekunder dan tersier. Kesimpulan dalam penelitian ini bahwa Notais yang bekerjasama dengan lembaga keuangan dengan mengirimkan surat permohonan kerjasama tidak sesuai dengan Undang Undang Jabatan Notaris pada Pasal 16 ayat (1) huruf a Tentang kemandirian Notaris serta aturan dalam kode etik Notaris pada Pasal 4 ayat (3) Tentang larangan kegiatan pemasaran yang termasuk dalam promosi diri dalam bentuk media cetak. Sedangkan dalam hal Notaris bekerjasama dengan perorangan tidak sesuai dengan UUJN pada Pasal 16 Ayat 1 huruf a dan huruf m, yaitu akta harus dibacakan kepada penghadap kecuali penghadap menghendaki agar akta tersebut tidak dibacakan karena penghadap telah membaca sendiri. Kata-kata Kunci: Notaris, Kerjasama, Sanksi